IPMS project shares monitoring and evaluation approach with Ethiopian Agricultural Growth Program - Gebremedhin, Berhanu (International Livestock Research Institute, 2012)
In November 2011, Berhanu Gebremedhin of ILRI/IPMS Project trained staff of the Ethiopian Agricultural Growth Program (AGP) on results-based monitoring and evaluation (November 28-December 3 2011 in Debrezeit Ethiopia). He outlined the main topics covered in the workshop: An introduction to results-based M&E; the development of a logic model and performance framework of a project; the performance measurement framework; the need for participatory M&E with stakeholders and how to do this; the selection and specification of indicators; data collection and analysis; the production and dissemination of of timely M&E reports; and the institutionalization of M&E and M&E units. He concludes by emphasizing the focus of the training- it was a training of trainers event - the participants are expected to train on their colleagues; they are also expected to lead M&E efforts at the regional level - guiding implementation as well as writing reports.